Penguatan UMKM Puri Farm Living Melalui Diversifikasi Produk Turunan Susu Kambing - Rahmat, Anni; Kurniati, Yuni; Noviasri, Rizky; Eko Wijanarko, Danang; Arifia Insani, Dzafif; Maulana, Firman; Nafisah, Salwa; Pratiwi, Hida (LPPM Universitas Trunojoyo Madura, 2025)
This community service program was implemented to strengthen the competitiveness of the Puri Farm Living association in Tuban Regency, which operates in the dairy goat farming sector. The main challenges faced were the limited market for fresh goat milk, low shelf life, and high competition among farmers following the Covid-19 pandemic. To address these issues, diversification of derivative products such as kefir, crackers, and goat milk soap was carried out. This diversification aimed to increase added value, expand the market, and improve the sustainability of farmers' businesses. The methods used included problem identification, technology transfer, training, mentoring, and evaluation. The results of the activity showed an increase in partners' skills in processing goat milk into value-added products, an increase in selling prices from IDR 25,000–30,000 per liter to IDR 40,000–50,000 per liter, and the opening of marketing opportunities through marketplaces and social media. Thus, this program not only impacted Puri Farm Living's economy but also strengthened local-based MSMEs.Keywords: Up to six keywords should also be included.